Building a natural sounding Text-To-Speech system for the Nepali language: research and development challenges and solutions - Bajracharya, Roop Shree Ratna; Regmi, Santosh; Bal, Bal Krishna; Prasain, Balaram (Gipan, 2019)
Text-to-Speech (TTS) synthesis has come far from its primitive synthetic monotone voices to more natural and intelligible sounding voices. One of the direct applications of a natural sounding TTS systems is the screen reader applications for the visually impaired and the blind community. The Festival Speech Synthesis System uses a concatenative speech synthesis method together with the unit selection process to generate a natural sounding voice. This work primarily gives an account of the efforts put towards developing a Natural sounding TTS system for Nepali using the Festival system. We also shed light on the issues faced and the solutions derived which can be quite overlapping across other similar under-resourced languages in the region.